Is the relationship between mast‐seeding and weather in oaks related to their life‐history or phylogeny?. Issue 10 (1st September 2016) - Koenig, Walter D.; Alejano, Reyes; Carbonero, Maria Dolores; Fernández‐Rebollo, Pilar; Knops, Johannes M. H.; Marañón, Teodoro; Padilla‐Díaz, Carmen M.; Pearse, Ian S.; Pérez‐Ramos, Ignacio M.; Vázquez‐Piqué, Javier; Pesendorfer, Mario B.
Abstract: Although the functional basis of variable and synchronous seed production (masting behavior) has been extensively investigated, only recently has attention been focused on the proximate mechanisms driving this phenomenon. We analyzed the relationship between weather and acorn production in 15 species of oaks (genus Quercus ) from three geographic regions on two continents, with the goals of determining the extent to which similar sets of weather factors affect masting behavior across species and to explore the ecological basis for the similarities detected. Lag‐1 temporal autocorrelations were predominantly negative, supporting the hypothesis that stored resources play a role in masting behavior across this genus, and we were able to determine environmental variables correlating with acorn production in all but one of the species. Standard weather variables outperformed "differential‐cue" variables based on the difference between successive years in a majority of species, which is consistent with the hypothesis that weather is linked directly to the proximate mechanism driving seed production and that masting in these species is likely to be sensitive to climate change. Based on the correlations between weather variables and acorn production, cluster analysis failed to generate any obvious groups of species corresponding to phylogeny or life‐history. Discriminant function analyses, however, were able to identify the phylogenetic section to which the species belonged and, controlling for phylogeny, the length of time species required to mature acorns, whether they were evergreen or deciduous, and, to a lesser extent, the geographic region to which they are endemic. These results indicate that similar proximate mechanisms are driving acorn production in these species of oaks, that the environmental factors driving seed production in oaks are to some extent phylogenetically conserved, and that the shared mechanisms driving acorn production result in some degree of synchrony among coexisting species in a way that potentially enhances predator satiation, at least when they have acorns requiring the same length of time to mature.